2014
DOI: 10.1002/hbm.22575
|View full text |Cite
|
Sign up to set email alerts
|

The role of testosterone and estradiol in brain volume changes across adolescence: A longitudinal structural MRI study

Abstract: It has been postulated that pubertal hormones may drive some neuroanatomical changes during adolescence, and may do so differently in girls and boys. Here, we employ growth curve modeling to directly assess how sex hormones (testosterone (T) and estradiol (E2)) relate to changes in subcortical brain volumes utilizing a longitudinal design. 126 adolescents (63 girls), ages 10 to 14, were imaged and restudied ~2 years later. We show, for the first time, that best-fit growth models are distinctly different when u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
186
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(193 citation statements)
references
References 60 publications
6
186
0
1
Order By: Relevance
“…In frontal and parietal cortex, this peak occurs around 10–11 years of age in girls, while the peak in boys is shifted about one year later (Giedd et al, 1999), which may relate to the tendency for girls to start puberty earlier than boys (Lenroot et al, 2007). When controlling for age, both pubertal hormones and stage of puberty correlate with changes in gray matter across adolescent development in disparate regions of cortex (De Bellis et al, 2001), including in the frontal cortex (Bramen et al, 2011; Gogtay et al, 2004; Herting et al, 2014; Herting et al, 2015; Koolschijn et al, 2014; Neufang et al, 2009; Peper et al, 2009a; Raznahan et al, 2010). For example, in a longitudinal study in which adolescent girls and boys were scanned once during early puberty and a second time during late puberty, there were effects of rate of change in pubertal status and sex in various subregions of the temporal, frontal, and occipital cortices (Herting et al, 2015).…”
Section: How Does the Neurobiology Of The Associative Neocortex Chamentioning
confidence: 99%
“…In frontal and parietal cortex, this peak occurs around 10–11 years of age in girls, while the peak in boys is shifted about one year later (Giedd et al, 1999), which may relate to the tendency for girls to start puberty earlier than boys (Lenroot et al, 2007). When controlling for age, both pubertal hormones and stage of puberty correlate with changes in gray matter across adolescent development in disparate regions of cortex (De Bellis et al, 2001), including in the frontal cortex (Bramen et al, 2011; Gogtay et al, 2004; Herting et al, 2014; Herting et al, 2015; Koolschijn et al, 2014; Neufang et al, 2009; Peper et al, 2009a; Raznahan et al, 2010). For example, in a longitudinal study in which adolescent girls and boys were scanned once during early puberty and a second time during late puberty, there were effects of rate of change in pubertal status and sex in various subregions of the temporal, frontal, and occipital cortices (Herting et al, 2015).…”
Section: How Does the Neurobiology Of The Associative Neocortex Chamentioning
confidence: 99%
“…Tanner stages in a sample of males and females (ages 7 to 22 years) were noted to predict changes in subcortical volume of several structures including the hippocampus, amygdala, and caudate (Goddings et al 2013). In a sample of 126 adolescents (ages 10 to 14 years) Hertig et al (2014) employed growth curve modeling to examine how testosterone and estradiol relate to changes in subcortical brain volumes obtained in a longitudinal design 2-years apart. Hormonal levels and Tanner Stage predicted WM and right amygdala growth for males and females across adolescence independent of age.…”
Section: Hormonal Modulationmentioning
confidence: 99%
“…Furthermore, these studies suggest that underlying hormonal changes may, in part, explain why pubertal status accounts for some of the variance in brain development. Structural MRI (Bramen et al, 2012; Bramen et al, 2011; Herting et al, 2014; Peper et al, 2009), diffusion tensor imaging (Herting, Maxwell, Irvine, & Nagel, 2012), and fMRI (Goddings et al, 2012; Klapwijk et al, 2013; Op de Macks et al, 2011) studies have found relationships between sex steroids and brain anatomy and activity, respectively, in healthy adolescent samples. Pubertal maturation may be particularly relevant to the development of brain systems underlying social and reward-related processing during adolescence.…”
Section: Introductionmentioning
confidence: 99%